Material Flow Cost Accounting to Enhance Sustainable Development: A Green Accounting Perspective - Maulana, Yusup; Purnama, Dendi; Rahmawati, Teti (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This study examined the impact of material flow cost accounting, corporate social responsibility, and green accounting on sustainable development. The contribution of this research includes (1) adding literature and insight into the impact of the application of material flow cost accounting, corporate social responsibility, and green accounting perspective on sustainability development, (2) contributing ideas for the government to establish policies or regulations to formulate sustainable development plans in the company in the form of mandates by applicable laws and regulations and related laws, (3) Provide input for companies in determining policies related to the implementation of green accounting, material flow cost accounting in supporting sustainable development. The research method uses descriptive and verification methods. The population in this study is coal companies listed on the Indonesia Stock Exchange for the 2016-2020 period, with a total of 26 companies. The final sample obtained as many as 100 observations from 2016-2020. The results found that material flow cost accounting, corporate social responsibility, and green accounting significantly positively affect sustainable development. The implications of this research can create far-reaching positive impacts, helping companies make decisions to prepare for sustainable development.